2019
DOI: 10.1186/s12906-019-2636-z
|View full text |Cite
|
Sign up to set email alerts
|

Larrea divaricata Cav. aqueous extract and nordihydroguariaretic acid modulate oxidative stress in submandibular glands of diabetic rats: a buccal protective in diabetes

Abstract: Background Oxidative stress is an imbalance between the levels of reactive oxygen species (ROS), reactive nitrogen species (RNS) and endogenous antioxidants. The aetiology and pathogenesis of several oral diseases are attributed to this process. The antioxidant enzymes secreted in the saliva by submandibular glands maintain oral health through the scavenging of ROS. The objective of this work was to study the capacity of an aqueous extract of L. divaricata (AE), and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Special attention has been focused in the activity of chemical compounds derived from natural products which, beside of show anti-inflammatory properties, have demonstrated anti-tumoral activity. For example, derivates from Larrea divaricate or Artemisa rubris plants are potent 5-lypo-oxygenase (5-LOH) inhibitors (206,207). In this regard, 5-LOH inhibitors such as embelin have shown a potent anti-tumoral activity by inducing cell death, cell cycle arrest, and inhibition of secretion of pro-inflammatory cytokines, growth factors, and metalloproteinases (208)(209)(210).…”
Section: Anti-inflammatory Drugs In Cancer Treatmentmentioning
confidence: 99%
“…Special attention has been focused in the activity of chemical compounds derived from natural products which, beside of show anti-inflammatory properties, have demonstrated anti-tumoral activity. For example, derivates from Larrea divaricate or Artemisa rubris plants are potent 5-lypo-oxygenase (5-LOH) inhibitors (206,207). In this regard, 5-LOH inhibitors such as embelin have shown a potent anti-tumoral activity by inducing cell death, cell cycle arrest, and inhibition of secretion of pro-inflammatory cytokines, growth factors, and metalloproteinases (208)(209)(210).…”
Section: Anti-inflammatory Drugs In Cancer Treatmentmentioning
confidence: 99%
“…In this sense, it has been demonstrated that the extract of L. divaricata exerts antioxidant activity through peroxidase (Px)-like, catalase (CAT)-like, and superoxide dismutase (SOD)-like as well as free radical scavenging activities [36]. Furthermore, the extract stimulates the secretion of Px in the submandibular glands of normal rats and modulates the level of antioxidant enzymes in the salivary glands of normal and streptozotocin (STZ)-induced diabetic rats [37][38][39]. The extract also has anti-tumor, immunomodulatory, and anti-inflammatory properties [40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the general population, the oral route is the main way of cadmium intake into the body [11,13] and animal studies show that this xenobiotic may induce pathological changes in the salivary glands, resulting among others from oxidative stress [7][8][9]. Moreover, other factors, to which individuals may be exposed, including tobacco smoke, ethyl alcohol, fluorides, ozone, titanium, laser light, and radiotherapy, as well as high-fat and high-protein diets, increase the amount of ROS in the oral environment [3,4,[38][39][40][41][42]. Destroying the oxidative/antioxidative balance in the oral cavity causes damage to the components of salivary gland cells and increases chronic local and systemic inflammation (by increasing the production and secretion of proinflammatory cytokines) and leads to dysfunction of the salivary glands, which can be seen in the form of changes in both the quantity and quality of salivary secretion.…”
Section: Introductionmentioning
confidence: 99%